Macroporous silicon: efficient antireflective layer on crystalline silicon (2011)
A macroporous silicon layer (ma-PS) electrochemically grown on crystalline silicon surface can be used as an efficient antireflective layer in optical devices as antireflection coating. In this work, we presented the ma-PS layers fabricated on crystalline silicon (c-Si) n-type and p +-type, obtained by electrochemical etching. The morphology, porosity, thickness of ma-PS layer can be adjusted by controlling the electrochemical formation conditions. The optical behaviour of the antireflective coating over the solar spectrum is determined, resulting in very low values of the normalized reflectivity coefficient (below ~1%). The reflectivity measurements were evaluated at 45° in the different samples of the ma-PS/c-Si